OPTIMALISASI IMPLEMENTASI KURIKULUM 2013 MELALUI WORKSHOP PENGEMBANGAN LKS IPA BERPENDEKATAN GUIDED-INQUIRY UNTUK MENGEMBANGKAN THINKING SKILL DAN SIKAP ILMIAH SISWA - Widowati, Asri; Anjarsari, Putri; Katriani, Laila (Universitas Negeri Yogyakarta, 2015)
The aims of this activity are to: (1) disseminating the results of researchfrom a team of stewards on the development of integrated science worksheetsguided inquiry based to develop thinking skills and scientific attitude in order tosupport the implementation of Kurikulum 2013; (2) improving the skills ofteachers in guiding students to form a concept (concept formation); (3) improvingtheskills of teachers in inquiry approach in worksheet; (4) improving thecreativity of teachers in developing worksheet. The target participant of this activity is 34 teacher members of MGMPIPA SMP/MTs Magelang regency. This activity is done in three stages, includingthestage of theoretical training, practical training phase and the evaluationphase. The methods used are: modeling (simulation), lectures, discus-sions, andworkshops. The results showed that the overall activity of PPM activity has beensuccessful in reaching the target activity. Most of the participants are alreadyskilled in guiding students to form a concept (concept formation) IPA. Mostparticipants also been able to apply the guided inquiry approach in studentworksheet. In addition, the final product student worksheet also shows most ofthe participants have been creative in developing worksheets with student worksheetdevelop their own (not copy and paste) and includes the development ofhigher order thinking skills in student worksheet